1992
DOI: 10.1002/art.1780350515
|View full text |Cite
|
Sign up to set email alerts
|

Selective deficiency of c1s associated with a systemic lupus erythematosus—like syndrome. Report of a case

Abstract: We describe a patient who developed a systemic lupus erythematosus-like syndrome characterized by bilateral malar erythema, antinuclear antibody, and anti-double-stranded DNA antibody. He was started on hemodialysis (3 timedweek) because of renal failure. He completely lacked total hemolytic complement (CH50) activity, which was subsequently determined to be due to the absence of the first component of complement (Cl). The specificity was further defined, by Ouchterlony analysis using anti-Cls antiserum, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 10 publications
(5 reference statements)
2
9
0
Order By: Relevance
“…Such analyses await the purification of native MASP-2 to homogeneity for direct comparisons with the recombinant protein. Importantly, our results already indicate that the MASP/MBL pathway of complement activation is qualitatively distinct from the C1 pathway, which is entirely dependent on the presence of both proteases (37,38).…”
Section: Discussionsupporting
confidence: 60%
“…Such analyses await the purification of native MASP-2 to homogeneity for direct comparisons with the recombinant protein. Importantly, our results already indicate that the MASP/MBL pathway of complement activation is qualitatively distinct from the C1 pathway, which is entirely dependent on the presence of both proteases (37,38).…”
Section: Discussionsupporting
confidence: 60%
“…In addition to a low level of serum C1s, patient III-1 and her brother patient III-2 showed significantly lower levels of serum C1r. Several previous reports showed that C1s deficiency was sometimes accompanied with C1r deficiency or abnormally low C1r (5,7). In the present study, we screened for abnormalities in the C1r gene, and demonstrated that patient III-1 has no abnormalities, at least in the coding sequence of this gene.…”
Section: Discussionsupporting
confidence: 48%
“…Several cases of human complement C1 deficiency have been reported (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), in which the deficiency was caused by the absence of the subcomponents C1q (6, 9 -13), C1r (3,4,8), C1s (7, 14 -17), or both C1r and C1s (5). The molecular basis for hereditary C1q deficiency is well defined, where homozygosity for nonsense mutations in the C1q A-chain and B-chain genes (6,10,12,13) and deletion, nonsense, and missense mutations in the C1q C-chain gene (10,11) have been demonstrated.…”
mentioning
confidence: 99%
“…Selective C1s deficiency has been previously reported in only two patients, both from Japan (2,3). Two other different molecular defects were detected in these cases.…”
Section: Discussionmentioning
confidence: 71%
“…Hereditary deficiency of classical component C2 is the most common deficiency of the complement system in Caucasians, whereas C4 or C1q deficiencies are rare. Only two cases of selective C1s deficiency have been reported to date, both in Japanese patients (1)(2)(3). Human C1s, a 85-kDa glycoprotein, has protease activity and is able to activate the C4 and C2 components of the classical pathway.…”
mentioning
confidence: 99%